Zeitpräferenz und Zeitkonsistenz: Zur Rationalität sequenzieller Entscheidungen; Time Preference and Time Consistency: On the Rationality of Sequential Choice - Hans-Peter Weikard (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– On the Rationality of Sequential ChoiceThe paper discusses the problem of discounting, time preference, and time consistent decision making. While a constant pure rate of time preference leads to consistent consumption plans, other discounting schemes - like hyperbolic discounting - do not. Using a so-called money pump argument, time inconsistencies can be shown to be irrational. The paper also explores the use of a hedonic utility concept to explain sequential choice behaviour.
Keywords: 330; Zeitökonomie; Zeitkonsistenz; Intertemporale Entscheidung; Diskontierung; Rationalität